Analysis of the Priestley-Taylor α parameter for a bean crop - Garcia, A. [UNESP]; André, R. G B [UNESP] (My University, 2000)
This work deals with the Priestley-Taylor model for evapotranspiration in different grown stages of a bean crop. Priestley and Taylor derived a practical formulation for energy partitioning between the sensible and latent heat fluxes through the α parameter. Bowen ratio energy balance (BREB) was carried out for daily sensible and latent heat flux estimations in three different crop stages. Mean daily values of Priestley-Taylor α parameter were determined for eleven days during the crop cycle. Diurnal variation patterns of α are presented for the growing, flowering and graining periods. The mean values of 1.13 ± 0.33, 1.26 ± 0.74, 1.22 ± 0.55 were obtained for a day in the growing, in the flowering and for graining periods, respectively. Eleven days values of α are shown and gave a mean value of 1.23 ± 0.10 which agree on the reported literature.
Keywords: Bowen ratio; Energy balance; Equilibrium rate; Phaseolus vulgaris (L.)